THE ROLE OF PROPERTY AND LAND TAXES IN EXPANDING LOCAL BUDGET REVENUES AND WAYS TO IMPROVE THEM - Саидов Бобур Чориевич (Web of Journals Publishing, 2024)
In the thesis, there are a number of problems in taxing real estate in the process of ensuring transparency in the formation of local budget revenues and improving the local tax calculation mechanism in our country. Failure to fully fulfill tax obligations by taxpayers, failure to pay local taxes on time and increase in tax arrears have a negative impact on the formation of local budget revenues, unification of property and land tax and gradual introduction of real estate tax instead, mechanism of local tax calculation in the tax administration system There are situations such as the use of modern information technologies, and it is important to develop ways to solve them and find practical solutions.
Keywords: property tax, land tax, price, cadastral value, market value of property, real estate, local budget, local government, tax object, tax base, tax rate and tax amount.